Psychological and Philosophical Problems of Tolerance - Rubskyi, V. M. (Anthropological Measurements of Philosophical Research, 2024)
Purpose. The purpose of the article is to formulate the uncontroversial principle of tolerance, taking into account the internal philosophical and psychological difficulties associated with its implementation in practice. Theoretical basis. The author proceeds from the insoluble problem of the very concept of "tolerance" and its psychological implementation. Not classical, but post-metaphysical psycho-religious method of promoting the idea of tolerance is proposed. This method was stated in the works by J. Derrida, P. Ricker, J. Caputo, G. Vattimo, R. Kearney, A. Shepherd, E. Newman, M. Moyaert, and others. The historical Christian type of tolerance (implementation of the principle of love for one’s neighbour) retains a significant potential for hidden aggression. This can be traced in the texts of the Holy Scripture and the fathers of the church. The division into friends and strangers based on the principle of confession remains relevant to this day. In addition, the religious component of tolerance tends to present it as self-worth, and not just an important socio-psychological parameter. The author points out that the application of Christian post-metaphysical approaches to this problem is the most philosophically coherent and psychologically effective. Originality. The article examines the internal semantic paradox of the idea of tolerance and methods of its promotion. The promotion of tolerance gives a rise to the suspicion of intolerance, which, being inherently intolerant, turns out to be a necessary component of the spread of the idea of tolerance. Typology of methods of introduction and promotion of tolerance (authoritarian, passive, psychological and religious), their main disadvantages and advantages are given. The main problems arising only at the level of philosophy and psychology are indicated. Conclusions. Historical Christianity is ineffective in achieving tolerance for a number of reasons: it is not sufficiently attentive to the individual, as it preserves the reasoning about the person in the categories of social formations (chosen people, etc.). The reality of God in classical texts was manifested by His violence in the past or in the future. The metaphysical basis of the principle of tolerance and the post-metaphysical understanding of hospitality return tolerance to its natural origin and provide a relevant basis for both interreligious dialogue and the removal of psychological tension between different cultural codes. The former models, which are proposed in the UNESCO Declaration, have a number of internal contradictions and are not effective enough in practice.